IMPLEMENTATION OF CONTROL ALGORITHMS IN BALL MAGNETIC LEVITATION SYSTEM TO IMPROVE SYSTEM PARAMETERS - Loo Hui , Shiong (Universiti Teknologi PETRONAS, 2012)
Magnetic Levitation System (Maglev) is an approach which is currently widely applied in different areas like semiconductor, transportation, power generation, household appliances and etc. Since Magnetic Levitation System is a highly non-linear system, constructing a successful controller which has robust performance becomes a big challenge. The most conventional method of building Maglev is PID controller. However findings of controller’s parameters which are